PELAKSANAAN KOORDINASI DALAM RANGKA MERAIH PENGHARGAAN ADIPURA DI KABUPATEN PASAMAN - Mardhiyah Yunus; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Adipura trophies a great achievement for a local chief. Not only the achievements, but also Adipura trophy is the prestige for the region it self. For the first time Pasaman was awarded adipura trophies in 2013 and then successfully for the second time in 2014 and became the only district/city are awarded in the province of West Sumatra.This achievement is the result of cooperation with the relevant agencies that assigned through the regent decree about the establishment of a coordination team of healthy city / Adipura. This study aims to identify and analyze the implementation of coordination in order to achieve the Adipura award in Pasaman and the factors that influence it. The concept theory that used is the Stoner coordination concept. It means that the better coordination includes four indicators, planning, communication, schedule of work, and supervision. This study used a qualitative descriptive study. In collecting the data, researchers use interviewing techniques, observation, and documents. Informants were taken using snowball sampling technique. The result of this research is showed that the implementation of coordination in the Adipura award has been implemented optimally. The implementation of coordination has covered all four indicators. It is influenced by the high commitment of heads of regions and their incentive funds budgeted forthe implementation of this coordination. Keywords: Implementation, Coordination, and Adipura